The Impact of Institutional Changes on the Halal Food and Beverage Certification Process in Indonesia - Abdul Mujib; Nikmatul Masruroh (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2025)
This paper aims to first describe the halal certification process for food and beverage products that has been carried out by LPPOM MUI. Second; explore the process of institutional change in halal certification of food and beverage products. Third; the impact of the presence of Law No. 33 of 2014 on halal certification institutions, business actors and consumers. These objectives are achieved using descriptive qualitative research. In presenting the data, it is discussed in detail using descriptions and narratives that can illustrate the results of the research. The results of the discussion of this paper are first, there are changes in procedures for submitting certification of food and beverage products, Second, the process of institutional change in food and beverage certification is still complicated and it seems that there has not been a complete institutional change, because in general it has not changed from the old pattern, third, the impact of institutional change is the cycle of Indonesian halal food products, because initially halal products were only based on MUI fatwas but now also refer to Law No. 33 of 2014.